A qualitative analysis of the documentation of DSM-5 Cultural Formulation Interviews with non-native speaking patients in a Swedish mental health care setting - Wallin, Malin Idar; DeMarinis, Valerie; Nevonen, Lauri; Bäärnhielm, Sofie (Frontiers in Psychiatry, 2024)
Cultural variety in expressed symptom presentations of mental health problems creates difficulties in transcultural diagnostic assessment. These emphasize the need of culturally sensitive diagnostic tools like the Cultural Formulation interview (CFI). Although the CFI is being implemented worldwide there is a lack of studies analysing what kind of information it provides when used with new patients in routine psychiatric assessments, and how CFI information contributes to diagnostic evaluations. This study aimed to find out what information the CFI questions revealed when used with non-native Swedish speaking patients, as part of a routine clinical psychiatric assessment in an outpatient clinic in Sweden. We also wanted to understand how the CFI may facilitate identification of psychiatric diagnoses among non-native speaking patients. Interpreters were used in the consultations when needed. Through qualitative thematic analysis, we found that the CFI information contained contextualized descriptions of dysfunction and current life conditions, as well as expressions of emotions, often described along with somatic terms. Our results indicate that the narrative approach of the CFI, giving contextualized information about distress and functioning, can facilitate clinicians’ identification of psychiatric symptoms when language, psychiatric terms and understandings are not shared between patient and clinician.